The Need of Bringing Discovery Learning Models Based Traditional Games in Mathematics of Teaching Materials - Sam Isnardiantini; Budi Usodo; Soegiyanto Soegiyanto (Pancaran Pendidikan, 2018)
Mathematics has not been a finished product given to students, but it is the process constructed by students. Selecting the mathematic teaching material effectively by means of combining traditional game, will help students understand the mathematic content their teachers teach. The objectives of research were: (1) to package traditional game in mathematiclearning content significantly, (2) to include Javanese cultural traditional game into mathematic teaching discovery learning model. This study was a qualitative descriptive research based on interview, observation and document analysis. The result of research shows that discoveryof learning model and traditional game that can be considered as the innovation source in mathematic teaching material development for elementary school students. The topic of mathematics with unique traditional game for the development of discovery learning model for mathematic teaching material is important to develop as an effective learning source for elementary school students.